Superemission in vertically-aligned single-wall carbon nanotubes - Khmelinskii, Igor (2017)
Presently we used two samples of vertically aligned single-wall carbon nanotubes (VA SWCNTs) with parallelepiped geometry, sized 0.02 cm x 0.2 cm x 1.0 cm and 0.2 cm x 0.2 cm x 1.0 cm. We report absorption and emission properties of the VA SWCNTs, including strong anisotropy in both their absorption and emission spectra. We found that the emission spectra extend from the middle-IR range to the near-1R range, with such extended spectra being reported for the first time. Pumping the VA SWCNTs in the direction normal to their axis, superemission (SE) was observed in the direction along their axis. The SE band maximum is located at 7206 0.4 cm(-1). The energy and the power density of the superemission were estimated, along with the diffraction-limited divergence. At the pumping energy of 3 mJ/pulse, the SE energy measured by the detector was 0.74 mJ/pulse, corresponding to the total SE energy of 1.48 mJ/pulse, with the energy density of 18.5 mJ cm(-2)/pulse and the SE power density of 1.2 x 10(5) W cm(-2)/pulse. We report that a bundle of VA SWCNTs is an emitter with a relatively small divergence, not exceeding 3.9 x 10(-3) rad. We developed a theoretical approach to explain such absorption and emission spectra. The developed theory is based on the earlier proposed SSH theory, which we extended to include the exchange interactions between the closest SWCNT neighbors. The developed theoretical ideas were implemented in a homemade FORTRAN code. This code was successfully used to calculate and reproduce the experimental spectra and to determine the SWCNT species that originate the respective absorption bands, with acceptable agreement between theory and experiment. Published by Elsevier B.V.